2017
DOI: 10.1590/1984-0462/;2017;35;4;00011
|View full text |Cite
|
Sign up to set email alerts
|

O Impacto Do Traumatismo Dental E Do Comprometimento Estético Na Qualidade De Vida De Pré-Escolares

Abstract: Objective: To evaluate the impact of dental trauma and impaired esthetics on the quality of life (QoL) of preschool children and their relatives.Methods: Study conducted with 192 children aged 2 to 5 years in 11 preschools in Florianópolis, Santa Catarina, South of Brazil. Parents/caregivers completed a questionnaire on quality of life (Brazilian version of the Early Childhood Oral Health Impact Scales - B-ECOHIS), a socioeconomic survey, and then answered specific questions related to dental trauma. The subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 32 publications
1
8
0
5
Order By: Relevance
“…The most frequent trauma was enamel and dentin without pulp exposure: 65.5%, followed by enamel crack: 30.6%, in agreement with the findings of Gonçales et al 1 and Goettems et al 8 , but contrary to Jung et al 16 who found that the most identified forms of trauma were fractures involving only enamel and fractures involving enamel and dentin. Andersson et al 14,17 recommended that the fractured coronary fragment be stored in physiological saline for bonding (because it is a low-cost technique and satisfactory aesthetic results), or restoration with resin if collage was not feasible.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The most frequent trauma was enamel and dentin without pulp exposure: 65.5%, followed by enamel crack: 30.6%, in agreement with the findings of Gonçales et al 1 and Goettems et al 8 , but contrary to Jung et al 16 who found that the most identified forms of trauma were fractures involving only enamel and fractures involving enamel and dentin. Andersson et al 14,17 recommended that the fractured coronary fragment be stored in physiological saline for bonding (because it is a low-cost technique and satisfactory aesthetic results), or restoration with resin if collage was not feasible.…”
Section: Discussionsupporting
confidence: 89%
“…Although guidelines of the International Association of Dental Traumatology (IADT) recommend focusing on the treatment of acute dental injuries, other sequelae of trauma such as crown discoloration should be considered 1 . The treatment for dental trauma varies with each patient, degree of severity, or duration of trauma 5 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 14 15 ] In Brazil, several studies in different parts of the country (e.g., Minas Gerais, Paraíba, Pernambuco, Santa Cantarina) have demonstrated high occurrence of traumatic dental injuries among children; however, no study in the State of Sergipe has focused its attention to the knowledge of some future health professionals, mainly considering the high prevalence (40.5%) of dental trauma in Sergipe. [ 16 17 18 19 ] Hence, this study investigated the effect of educational intervention among undergraduate students, from three health courses, of a Federal University in Brazil, including lecture presentation and question-and-answer sessions, to promote awareness regarding emergency measures concerning tooth avulsion and tooth crown fractures.…”
Section: Introductionmentioning
confidence: 99%
“…When analyzing the level of agreement (ICC) of the different items, individually, they varied from weak to substantial, and the best agreement (ICC = 0.72) was observed in the "avoid smiling due to teeth appearance" item [8]. This finding may be attributed to the growing aesthetic concern of parents, motivated by media and society, who end up by excessively worrying about the appearance of their children's front teeth, possibly by malicious comments from school and neighborhood peers, denoting, in some cases, bullying [26]. There are no studies in the literature relating to aesthetic commitment to quality of life in primary teeth, although preschool children attribute behavioral characteristics to other children based on their appearance [27].…”
Section: Discussionmentioning
confidence: 96%